L'archivio di Odoardo Beccari Indagini naturalistiche tra fine '800 e inizio '900 - Biagioli, Beatrice (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2008)
Botanist, zoologist, explorer and anthropologist: between the second half of the nineteenth century and the early decades of the twentieth, Odoardo Beccari was all this and more. His fame continues to be linked primarily with the scientific expeditions to south-east Asia, and Borneo in particular, and his work on Palms, as well as his skill as a draughtsman and photographer. The material conserved in his personal archive is of fundamental importance for a reconstruction, not only of the his scientific career but also of his private life. This inventory finally provides us with the key to find our way around a very significant body of documents ranging from correspondence, notes and preparatory materials to manuscript drafts, travel journals, map sketches, drawings and photographs.